Rapid Spontaneous Total Fusion of Neuropathic Arthropathy of the Wrist After Limited Intercarpal Arthrodesis: A Case Report and Brief Literature Review - Xu, Ke; Wu, Guangzhi; Zhang, Weizhong; Yu, Wei; Cui, Shusen; Zhang, Zhan (Frontiers in Surgery, 2022)
Background: Previous reports on the treatment of neuropathic arthropathy of the wrist were generally conservative, with few case reports of treatment with osteoarticular surgery. Case presentation: A 25-year-old right-handed male complained of unpainful swelling of the dorsal aspect of his right wrist for 3 years. He was at that time diagnosed with synovitis and radiocarpal arthritis. The patient underwent a partial Four-Corner Arthrodesis and Synoviectomy to preserve motor function. And over the next 2 months, his right wrist developed painful redness, with progressive swelling and stiffness. Rheumatoid arthritis, tuberculosis arthritis and infectious diseases were ruled out in this case. MRI indicated that he had Chiari II syringomyelia so the patient was eventually diagnosed with destructive neuropathic arthropathy (syringomyelia). After 2 months of conservative treatment, the patient’s right wrist spontaneously and completely fused and the pain disappeared. Conclusion: Neuropathic arthropathy of the wrist is a rare but clinically significant disease due to its effect on the function of the active limb. Surgeons should rule out a diagnosis of it when treating patients with wrist swelling and osteoarticular abnormalities, otherwise limited intercarpal arthrodesis should not be taken as a treatment option. Inappropriate partial surgery is likely to lead to rapid total fusion of neuropathic arthropathy of the wrist.